Visual Loss Induced by Adalimumab Used for Plaque Psoriasis - Norman Saffra; Konstantin Astafurov (Karger Publishers, 2017)
A 61-year-old Caucasian male with severe plaque psoriasis without joint involvement was initiated on adalimumab therapy. Shortly thereafter he presented to the emergency room with acute loss of vision in the right eye. A comprehensive systemic workup was instituted which included magnetic resonance imaging (MRI) with and without gadolinium of the brain and orbits. MRI revealed findings that were consistent with CNS demyelination and retrobulbar optic neuritis. Immediate cessation of adalimumab was instituted without any other systemic therapy. Complete return of vision occurred within 6 weeks. No additional psoriatic or neurologic treatment was instituted, and the patient has remained stable now for 14 months.